Odpowiedź :
równania:
a)x3-x2+x-1=0
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5
b)3x+6x-4x-12=0
5x=12/:5
x=12/5
c)9x-4x-6x+4=0
-x=-4/(-1)
x=4
d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2
e)3x+2x-4x-4=0
x=4
f)6x+2x-2x-1=0
6x=1/:6
x=1/6
g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2
h)3x-√6x-√3x+3=0
3x-√3x+3=0
a)x3-x2+x-1=0
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5
b)3x+6x-4x-12=0
5x=12/:5
x=12/5
c)9x-4x-6x+4=0
-x=-4/(-1)
x=4
d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2
e)3x+2x-4x-4=0
x=4
f)6x+2x-2x-1=0
6x=1/:6
x=1/6
g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2
h)3x-√6x-√3x+3=0
3x-√3x+3=0
a)x3-x2+x-1=0
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5
b)3x+6x-4x-12=0
5x=12/:5
x=12/5
c)9x-4x-6x+4=0
-x=-4/(-1)
x=4
d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2
e)3x+2x-4x-4=0
x=4
f)6x+2x-2x-1=0
6x=1/:6
x=1/6
g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2
h)3x-√6x-√3x+3=0
3x-√3x+3=0
chyba tak mam nadzieje że dobrze;)
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5
b)3x+6x-4x-12=0
5x=12/:5
x=12/5
c)9x-4x-6x+4=0
-x=-4/(-1)
x=4
d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2
e)3x+2x-4x-4=0
x=4
f)6x+2x-2x-1=0
6x=1/:6
x=1/6
g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2
h)3x-√6x-√3x+3=0
3x-√3x+3=0
chyba tak mam nadzieje że dobrze;)